ENTREPRENEURSHIP CERTIFICATE TRAINING AND OBSERVATIONS AT ÇUKUROVA UNIVERSITY - Guzel, Emin (PEOPLE: International Journal of Social Sciences, 2018)
The aim of this study is to develop the solution proposals by identifying the main trends and the problems that students in the attend entrepreneurship certification education courses in Cukurova Universities. The entrepreneurship priority of the students participating in the curriculum was investigated according to the professional groups, taking into account the legal regulations, supports and development targets published in this direction. For this reason, the situation of students applying for a three-year project, which started in 2015 and completed in June 2018, was taken into account. In the project, 30 programs were opened in six semesters and 590 students graduated. Considering the entrepreneurial tendencies of the participants who graduated from the course program, the engineering faculty was ranked first and vocational high school students ranked second. The biggest problem that has been encountered is to reach the venture capital required for the entrepreneur who wants to establish the first business.